Oxytocin Ameliorates the Immediate Myocardial Injury in Heart Transplant Through Down Regulation of the Neutrophil Dependent Myocardial Apoptosis - Al-Amran, F. Fadhil (Medknow Publications & Media Pvt Ltd, 2014)
Cardiac oxytocin (OT) is structurally identical to that found in the hypothalamus, which thereby indicates that cardiac OT is derived from the same gene and is an active form of OT. The abundance of OT and OT receptors in atrial myocytes shows that, directly and/or via the release of the cardiac hormone atrial natriuretic peptide, OT can regulate the force of cardiac contractions. Previous studies have demonstrated the role of OT in the myocardial inflammatory response. The mechanism by which OT elicits protective myocardial effects in the immediate post-transplantation period is not yet clear, and the role of the early phase inflammatory elements in this mechanism has not yet been studied. As a result, in this study, we have investigated the anti-inflammatory effects of OT on myocardial protection in the immediate post-transplantation period. METHODS: Adult male Albino rats were grouped into: Sham, Control, and OT-treated groups. The control and treated groups sustained cervical heterotopic heart transplant. Myocardial injury was assessed by measuring: Plasma cardiac troponin I, myocardial proinflammatory cytokines, and histopathological assessment for score of injury, and degree of apoptosis. Myocardial myeloperoxidase, neutrophil infiltration, and neutrophil chemotactant agents, reactive oxygen species, and reactive nitrogen species formation all were measured in the myocardium after 3 hour of reperfusion to assess the neutrophil-dependant myocardial injury and the mechanism involved. RESULTS: Oxytocin down-regulates the neutrophil chemotactant agents the KC/CXCL1 and MIP-2/CXCL2 which recruit less neutrophil into myocardium, this decrement in myocardial PMN infiltration is associated with less reactive oxygen species and reactive nitrogen species formation in the myocardium after 3 hours of global ischemia reperfusion. These oxytocin-induced down-regulation inflammatory and oxidative processes will end in less myocardial injury through impedance in the post-myocardial ischemia/reperfusion apoptotic process. CONCLUSION: Oxytocin ameliorates myocardial injury in heart transplant through down-regulation the myocardial inflammatory response, reactive oxygen species, and neutrophil-dependant myocardial apoptosis.